The changing tenor of English in multicultural postcolonial Malaysia - Ganakumaran Subramaniam, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
It is widely accepted that living languages change over time and space. By this measure it can be stated that the English used in environments different from its origin, would adjust and change to suit its new environments. In the context of Malaysia changes to the institutional role and status of the English language has waxed and waned to a point of near extinction only to re-emerge stronger in the 21st century. However the politics of language policies has not deterred its users from consciously and unconsciously reorienting the language system so that it remained relevant and meaningful to its users. This paper examines some of the challenges and concerns that confront the use and users of English in postcolonial contexts. More specifically the paper discusses some of the changes embodied in Malaysian English as a result of characteristics brought to it by the new language users, their relationships to each other, and their purposes. In discussing the tenor of postcolonial English, the paper argues that changes inscribed in these new varieties are products of real needs and realities in new language speaking contexts.